Comparison of the Effectiveness of Cognitive-Behavioral Therapy and Acceptance and Commitment Therapy on Job Burnout and Psychological Well-being of Nurses - Ashoori, Naghmeh; Rafiepoor, Amin; Sabet, Mehrdad (Psychology of Woman Journal, 2024)
Objective: The aim of the present study was to compare the effectiveness of Cognitive-Behavioral Therapy (CBT) and Acceptance and Commitment Therapy (ACT) on job burnout and psychological well-being among nurses. Methods and Materials: The research method was quasi-experimental, employing a pre-test, post-test, follow-up design with a control group. The statistical population of this study included all female nurses of Hazrat Rasoul Akram Hospital in Tehran in the spring of 2023, from which 45 individuals were selected using purposive sampling and were randomly assigned to two intervention groups and one control group. The research instruments included the Maslach Burnout Inventory (Maslach et al., 1996) and the Ryff Psychological Well-being Scale - Short Form (Ryff, 1989). After conducting 8 sessions of Cognitive-Behavioral Therapy and 8 sessions of Acceptance and Commitment Therapy for the intervention groups, the data were analyzed using SPSS software version 24. Findings: Cognitive-Behavioral Therapy and Acceptance and Commitment Therapy had significant effects on job burnout and psychological well-being in the intervention groups (P < 0.01), and the differences in the mean scores of job burnout and psychological well-being among the Cognitive-Behavioral Therapy groups, Acceptance and Commitment Therapy groups, and the control group were statistically significant (P < 0.01). Conclusion: The results indicated that both Cognitive-Behavioral Therapy and Acceptance and Commitment Therapy are effective in improving job burnout and psychological well-being among nurses. It is recommended that healthcare administrators and specialists conduct empowerment programs with a Cognitive-Behavioral or Acceptance and Commitment approach.